Eugen Fink’s Critique of Husserlean Phenomenological Language - Tomashpolskaia, Natalia (2021)
In this article I consider Eugen Fink’s critique of Husserlean approach to language in phenomenology, first of all in the ‘middle’ and ‘late’ periods of Husserlean works since Ideas I. Fink was Husserl’s student and assistant and, also, he was influenced by Heidegger’s ideas. In his works he criticized insufficient attention and unworked position to language in Husserl’s works. He believed that language is very important to the whole theory of phenomenology, that we cannot carry out true phenomenological reduction without clarifying what language is, how it is related to our thinking, is it possible to think without language and is it possible to carry out a complete phenomenological reduction.